2018
DOI: 10.2174/1573399813666170829163442
|View full text |Cite
|
Sign up to set email alerts
|

Study of Irisin Hormone Level in Type 2 Diabetic Patients and Patients with Diabetic Nephropathy

Abstract: There is a decrease in serum irisin level in type 2 diabetic patients with even more significant reduction in patients with diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 0 publications
6
17
0
4
Order By: Relevance
“…Additionally, the Moreno-Navarrete et al [ 54 ] study showed that plasma levels of irisin and the expression of the FNDC5 gene in muscle and fat tissue in obese patients with type 2 diabetes and obesity are reduced. Very similar results were obtained by Shelbaya et al [ 55 ]. In addition to the lower concentration of irisin in the blood of patients with type 2 diabetes compared to healthy people, they revealed the negative correlations with creatinine, systolic, and diastolic blood pressure, BMI, ACR, and HbA1c [ 55 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, the Moreno-Navarrete et al [ 54 ] study showed that plasma levels of irisin and the expression of the FNDC5 gene in muscle and fat tissue in obese patients with type 2 diabetes and obesity are reduced. Very similar results were obtained by Shelbaya et al [ 55 ]. In addition to the lower concentration of irisin in the blood of patients with type 2 diabetes compared to healthy people, they revealed the negative correlations with creatinine, systolic, and diastolic blood pressure, BMI, ACR, and HbA1c [ 55 ].…”
Section: Discussionsupporting
confidence: 91%
“…Very similar results were obtained by Shelbaya et al [ 55 ]. In addition to the lower concentration of irisin in the blood of patients with type 2 diabetes compared to healthy people, they revealed the negative correlations with creatinine, systolic, and diastolic blood pressure, BMI, ACR, and HbA1c [ 55 ]. Bonfante et al [ 56 ] found in their research that a higher level of irisin is associated with a better metabolic profile of obese people.…”
Section: Discussionsupporting
confidence: 91%
“…The reduction in irisin level has been detected in stage 5 of CKD, although the reduction in muscle mass and/or the significant reduction in renal function may affect irisin levels. Nevertheless, substantial reduction was observed in diabetic nephropathy patients [ 167 ]. Recently, reduction in FNDC5 expression was significantly associated to enhanced SkM autophagy and atrophy under urotensin II (UII) induction in vivo in a mouse model of CKD and in vitro in C2C12 cells.…”
Section: Fndc5/irisin and Autophagymentioning
confidence: 99%
“…It has previously been shown that irisin mitigates expression of pro-inflammatory cytokines, to reduce oxidative stress and to possess anti-apoptotic effects [3]. In patients with diabetes mellitus, irisin levels were lower with regard to their non-diabetic counterparts and circulating levels were even more decreased when the disease was accompanied by other co-morbidities such as diabetic nephropathy [19,34]. Moreover, reduced levels of irisin were supposed to be related to diabetes mellitus and other metabolic diseases [33].…”
Section: Introductionmentioning
confidence: 99%